Intersubjectivity, Empathy and Education. A Phenomenological Approach - Sánchez Muñoz, Rubén (2021)
The aim of this paper is to describe from a phenomenological perspective: a) the relationships between intersubjectivity and the phenomenon of education; b) empathy as the basis and the foundation of intersubjective relationships; and c) the importance of empathy for education. The thesis to be defended states that every educational process of teaching and learning, whether in school, in the family or in society, needs the experiencing of others and empathy makes it possible to access this sort of experience. This experience is mediated by the body and develops into an intercultural, intersubjective and inter-corporeal dimension.